Bioactivity of Prosopis alpataco and Prosopis flexuosa flours: Healthy alternatives as ingredients for nutritional foods - Hoffmann, Elizabeth (2024)
Prosopis spp. Pods are a staple food among rural communities. The nutritionalcomposition, antioxidant activity and in vivo biological properties of P. alpataco Phil.And P. flexuosa DC., underutilized Prosopis species, were studied. High amount ofdietary fiber (>50%) and polyphenols (0.45-0.50g of gallic acid equivalents, GAE/100gflour) were detected. The content of aminoacids, minerals, and the profile of phenoliccompounds (PCs) were determined from pods. Among the most abundant PCs, (-)-epigallocatechin gallate, trans-picein and ε-viniferin were identified for the first time inProsopis species. In vivo study with zebrafish model revealed that pod extractsresulted in lower reactive oxygen species generation (up to 30%) compared to thecontrol group. Also, P. alpataco extract was able to inhibit enzymes associated withmetabolic syndrome progression: α-amylase, α-glucosidase and lipase (half maximalinhibitory concentration: IC50 1.93, 2.94 and 22 μgGAE/ml, respectively). The resultsevidence the potential value of this non-conventional flour as a promising ingredient forfunctional foods.